Method for measuring factors that affect the performance of pilots - Bandeira, Michelle C.G.S.P.; Correia, Anderson Ribeiro; Martins, Marcelo Ramos (Transportes, 2017)
This paper presents the development of a model of accident analysis according to the principal factors which influence aeronautical accidents that are able to assess any aircraft accident, taking into account human, organizational, environmental and airport infrastructure factors. The methodology of data collection of this research was through the literature, analysis of aircraft accident reports, technical visits to the center of certification of commercial aircraft pilots and interviews with industry experts. From this model, it is possible to evaluate the influence of these factors and identify the dependence and relationship existing, and how they influence the system. With the aid of Bayesian Networks technique, it is also possible to quantify the factors and assess which ones have more impact in the system. The results show the relationship between the factors that can influence the performance of the pilots and therefore can indicate how it may impact the success or failure of tasks related to flight procedures. The results also may indicate subsidies for mitigating actions, collaborating in the management of operational safety of air transport and assessing the overall impact of the factors that determine any accident.